(Re)reading the political conflict over HIV in South Africa (1999-2008): A new materialist analysis - Pienaar, Kiran (2014)
This article recasts a critical moment in the history of HIV/AIDS in South Africa: the struggle over the science of HIV that emerged under former South African President Mbeki (1999-2008). It compares how the Mbeki administration and prominent South African AIDS organisation, the Treatment Action Campaign (TAC) responded to the dominant scientific model of HIV/AIDS. Contrary to existing research, which presents the government and TAC's positions as polarised, this article draws attention to some important commonalities in their understandings of HIV. I argue that both parties were doing the 'boundary-work' of science (Gieryn, 1995, p. 404): tussling over the demarcation between science and non-science in order to assert the 'truth' about HIV/AIDS. In so doing, they constitute HIV as a biologically self-evident disease possessed of intrinsic attributes. The article draws on science studies and new materialist scholarship to query this conventional view and its presumption that disease is a static object that precedes political processes and practices. It argues instead that disease is made through politics and it traces some significant political practices that have contributed to making HIV/AIDS in South Africa in specific, sometimes damaging ways. © 2014 Macmillan Publishers Ltd.